Internet of vehicles : technologies and services for smart cities : 4th International Conference, IOV 2017, Kanazawa, Japan, November 22-25, 2017, Proceedings /: technologies and services for smart cities : 4th International Conference, IOV 2017, Kanazawa, Japan, November 22-25, 2017, Proceedings. (2017) - Unknown
No abstract available